Targeting Social Policy and Poverty Reduction: The Case of Social Safety Nets in Bangladesh. Issue 2 (1st June 2014) - Masud‐All‐Kamal, Md.; Saha, Choyon Kumar
<x xml:space="preserve">Abstract</x> Target‐based social safety net programs of Bangladesh aim to protect vulnerable people from crisis and to reduce chronic poverty through the direct transfer of food, resources, and cash. Though the country has been spending a vast amount of public funds for a large number of social safety net programs for several decades, the deserving extreme poor candidates are significantly being excluded and their poverty condition still remains high. This article explores the effectiveness of social safety nets to address chronic poverty and vulnerability, reviewing the theoretical literature and empirical findings. The review indicates that target‐based social safety net programs are facing challenges as an effective social policy for Bangladesh in freeing millions of people from vulnerability and extreme poverty because of administrative complexity, high cost, high leakages, mistargeting, weak governance, less transparency and accountability, political capture, and corruption in program implementation; these programs rather strengthen rent‐seeking patron‐clientelism and create a large number of intermediaries. It is therefore critical to redesign the safety net programs to achieve better outcomes and ensure their effectiveness.